Cyclic dominance emerges from the evolution of two inter-linked cooperative behaviours in the social amoeba. Issue 1881 (20th June 2018) - Shibasaki, Shota; Shimada, Masakazu
Abstract : Evolution of cooperation has been one of the most important problems in sociobiology, and many researchers have revealed mechanisms that can facilitate the evolution of cooperation. However, most studies deal only with one cooperative behaviour, even though some organisms perform two or more cooperative behaviours. The social amoeba Dictyostelium discoideum performs two cooperative behaviours in starvation: fruiting body formation and macrocyst formation. Here, we constructed a model that couples these two behaviours, and we found that the two behaviours are maintained because of the emergence of cyclic dominance, although cooperation cannot evolve if only either of the two behaviours is performed. The common chemoattractant cyclic adenosine 3′, 5′-monophosphate (cAMP) is used in both fruiting body formation and macrocyst formation, providing a biological context for this coupling. Cyclic dominance emerges regardless of the existence of mating types or spatial structure in the model. In addition, cooperation can re-emerge in the population even after it goes extinct. These results indicate that the two cooperative behaviours of the social amoeba are maintained because of the common chemical signal that underlies both fruiting body formation and macrocyst formation. We demonstrate the importance of coupling multiple games when the underlying behaviours are associated with one another.